Monolayer AsTe2: Stable Robust Metal in 2D, 1D and 0D. Issue 17 (1st August 2018) - Badalov, S. V.; Kandemir, A.; Sahin, H.
Abstract: The structural, phononic, and electronic properties of the monolayer structures of AsTe2 are characterized by performing density functional theory (DFT) calculations. Total energy optimization and phonon calculations reveal that single layers of the 2H‐AsTe2 and 1T‐AsTe2 phases form dynamically stable crystal structures. Electronic structure analysis also shows that both 2H and 1T phases have nonmagnetic metallic character. It is also predicted that the metallic nature of the ultra‐thin both 2H‐AsTe2 and 1T‐AsTe2 structures remain unchanged even under high biaxial strain values. For further examination of the dimensionality effect in the robust metallicity in 2D AsTe2 phases, electronic characteristics of 1D nanoribbons and 0D quantum dots are also investigated. It is found that independent from the dimension and crystallographic orientations 0D and 1D structures of 2H‐ and 1T‐AsTe2 structures have metallic behavior. It is found that single layers of AsTe2 are quite promising materials for nanodevice applications owing to the robust metallic character. Abstract : Ultra‐thin 2H‐ and 1T‐AsTe2 structures are dynamically stable metallic materials. Their robust metallic nature is an independent from (i) high compressive and tensile strains (ii) reduction of dimensionality from two‐ (2D) to one‐ (1D) and zero‐dimensional (0D) (iii) size and growth dynamics of 1D and 0D structures.